Fetus Amorphous Acardious – A Case Report - N. S. Kamakeri (Journal of Krishna Institute of Medical Sciences University)
Fetus amorphous acardious is a rare fetal malformation lacking a functional heart and bearing no resemblance to human embryos. The main differential diagnosis is with placental teratoma and is based on the degree of skeletal organization and umbilical cord formation. A 26 year old woman delivered a healthy newborn at 38 weeks of gestation by caesarian section. An amorphous mass covered with healthy looking skin was connected to the placenta with a short pedicle. Xray examination of the mass revealed the presence of vertebral column associated with ribs and pelvic bones and axial skeleton. Histopathological examination demonstrates the presence of cartilage, bone, adipose tissue, skin with adnexal structures and neural tissue.